Destination Image Recognition And Emotion Analysis: Evidence From User-Generated Content Of Online Travel Communities. (3rd July 2020) - Huang, Weidong; Zhu, Shuting; Yao, Xinkai
Abstract: The tourism destination image is an intangible value that enhances the internal and external spiritual value of the region. To improve tourist experiences and provide reference for relevant departments, we applied the GooSeeker web data crawler tool and Python data mining kit to crawl and analyze the representative online tourism community data. We conduct an empirical analysis through data from the online tourist community 'mafengwo'. The result, based on the user-generated content data analysis of online travel community, shows that the tourists' perception of the destination image, cognitive theme and emotional experience has different effects on the tourist experience. This research offers insights into destination image cognitive theme and traveler behavior habits, which can provide guidance for platform and destination managers.